The Relationship Between Depression, Loneliness, and Suicide Ideation on Adolescents and Young Adults: A Cross-sectional Study - Wiwik Widiyawati; Yuni Asri (PT.Mantaya Idea Batara, 2026)
Depression and loneliness are prevalent mental health concerns among adolescents and young adults and may increase the risk of suicidal ideation. Adolescence and early adulthood represent transitional developmental stages characterized by various psychosocial demands, which may heighten vulnerability to emotional distress. This study aimed to examine the relationship between depression, loneliness, and suicidal ideation among adolescents and young adults. A quantitative approach with a cross-sectional design was employed. The study population consisted of 462 individuals, from which 215 respondents were selected using simple random sampling. Data were collected using the Depression Anxiety Stress Scales (DASS-42) to measure depression levels, the UCLA Loneliness Scale Version 3 to assess loneliness, and the MINI Plus 5.0.0 to identify suicidal ideation. Data were analysed using Spearman’s rank-order correlation test. The results revealed a statistically significant positive correlation between depression and suicidal ideation (r = 0.376; p = 0.01), indicating a weak to moderate association. In contrast, loneliness was not significantly correlated with suicidal ideation (r = 0.10; p = 0.10). These findings suggest that depression plays a more substantial role in the emergence of suicidal ideation than loneliness. Therefore, suicide prevention strategies targeting adolescents and young adults should prioritize the early identification and management of depression while also strengthening psychosocial protective factors.